PELATIHAN DAN PENDAMPINGAN PEMBUATAN KATALOG PRODUK PADA UMKM MITRA POLINEMA DI DESA DUWET KECAMATAN TUMPANG KABUPATEN MALANG - Mahmudatul Himma; Diana Eka Poernamawati; Achmad Zaini; Ayu Sulasari; Muhamad Muwidha; Evi Suwarni (Jurnal Pengabdian kepada Masyarakat, 2024)
This community service aims at training and assistance in making product catalogs for polynema partner MSMEs in Duwet Village, Tumpang District, Malang Regency, which at that time there was still no porduk catalog available, so that marketing activities were still not optimal. The creation of this product catalog is expected as a means of promotion to introduce products made by Duwet Village residents to the wider community. This community service activity in the form of training and assistance in making product catalogs is divided into two stages, the first is that the Duwet village community will be given photography training to produce quality product images and the second stage is training on making layouts for photographic product catalogs. With this community service activity, it is hoped that the assisted villages can create product catalogs both print and digital for promotional facilities to increase sales volume so that the impact will be on improving the welfare of Duwet Village.   Keywords:MSMEs, Promotions, Product Catalogs